Nursing Practice With Menstrual and Fertility Mobile Apps. Issue 1 (January 2016) - McCartney, Patricia R.
Abstract : A search on any smart phone app store for menstruation, ovulation, or fertility trackers results in hundreds of choices of free or low cost apps. Women use these apps frequently. Our HIT expert, Dr. McCartney, shows they can be beneficial for clinical practice.